ANALISIS YURIDIS PELAKSANAAN PEMBERIAN GANTI RUGI DALAM PENGADAAN TANAH UNTUK PEMBANGUNAN BENDUNGAN DI KABUPATEN BOGOR: Juridical Analysis Of The Implementation Of Compensation In Land Procurement For Dam Construction In Bogor District - Dini Lindawati Wahyuni; Intan Nevia Cahyana (Faculty of Law, Universitas Trisakti, 2025)
Land acquisition for the construction of public infrastructure such as dams is a form of land acquisition for the public interest that must guarantee legal certainty and protection of citizens' rights to land. As a solution to reduce flooding, the government built a dam as a public interest project in Bogor Regency. Which requires the release of rights by providing fair and appropriate compensation. And the formulation of the problem is How is compensation given in land acquisition for the construction of the Cibeet and Cijurey Dams in Bogor Regency. This type of research is normative juridical which is descriptive-analytical. The data used are secondary data and primary data. Drawing conclusions with deductive logic. The results and conclusion of the analysis regarding the implementation of compensation at the land acquisition implementation stage are in accordance with applicable regulations. However, there are still differences of opinion regarding the amount of compensation so that strengthening is needed from various parties in its implementation so as not to cause social conflict